The effect of video blog as media on students' english speakinh skill: an experimental research at english department of universitas negeri padang - Andreza Jasveri; M. Zaim (Journal of English Language Teaching, 2020)
This research is quasi-experimental research is aimed to find out the effect of video blog as media on students’ speaking skill and the effectiveness of video blog as media on improving students’ speaking skill at English Department of Universitas Negeri Padang. The instrument of this research is speaking test that is conducted twice, pre-test and post-test. The test had 3 topics that student should pick one of them, the test will be rate by using rating score which adapted from Brown and Blaz. Based on the test data analysis by using independent sample test in SPSS 25, it state that the students’ who are taught by using video blog as media are better than students’ who are taught by using conventional media. The significance of the test is 0.000 which is lower than the significance level that is 0.05 with 5% of degree. Furthermore, is also found that the students’ score is improving especially for students in experimental class which gained 10.8 of their average score. . Key words: Speaking, Video Blog.